EKSPLORASI BUDAYA NTT DALAM NOVEL GERSON POYK - Imelda Oliva Wissang; Imelda Oliva Wissang; Arsiya Wanaeloh; Tobias Nggaruaka (JURNAL ILMIAH BAHASA DAN SASTRA, 2021)
This article aims to describe the exploration of NTT's culture in the novels by Gerson Poyk as one of the national writers, Angkatan `66. This NTT-born author writes novel literary works by raising cultural traditions as a characteristic, the identity of the NTT people, cultural traditions with the values ​​contained in them that are lived and preserved, although some have begun to disappear by the influence of modern culture. The uniqueness of Gerson Poyk is that he is able to raise the cultural background of NTT with its vast territory into his novels with a straightforward, expressive, and high aesthetic style of expression. Not only limited to cultural traditions but tourism development, agricultural cultivation, commercial crops, livestock, fisheries, handicrafts. Through a number of his novels, Gerson Poyk explores the culture that exists in the life of the people of NTT which can be used as a character of Indonesian culture. This research uses the theoretical basis of sociology of literature with the emphasis that the novel is actually a form of socio-historical embodiment, where novels can witness paintings of social and social reality. history, into a genre that is close to social phenomena. Using qualitative research methods in literature studies can describe, understand, and explain the exploration of NTT culture in the novel by Gerson Poyk. Exploration of NTT culture as a character of Indonesian culture in Gerson Poyk's novel, 1) exploring the cultural elements of the knowledge system towards the love of the NTT people to study, 2) exploring the cultural elements of the kinship and kinship system of the love of the NTT people to maintain relationships, 3) exploring the cultural elements of the system. livelihoods towards the love of the people of NTT doing work, 4) exploring the cultural elements of the religious system towards the love of the people of NTT in carrying out religious traditions, and 5) exploring elements of art culture towards the love of the people of NTT in the arts and culture.